2018
DOI: 10.1002/term.2606
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel composition and laser micropatterning to regulate sciatic nerve regeneration

Abstract: Treatment of peripheral nerve injuries has evolved over the past several decades to include the use of sophisticated new materials endowed with trophic and topographical cues that are essential for in vivo nerve fibre regeneration. In this research, we explored the use of an advanced design strategy for peripheral nerve repair, using biological and semi-synthetic hydrogels that enable controlled environmental stimuli to regenerate neurons and glial cells in a rat sciatic nerve resection model. The provisional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The degraded hydrogel is then flushed out of the construct to generate microchannels. Hydrogels used for laser degradation can be made from natural polymers such as silk (20), collagen (21,22) and elastin (22), synthetic polymers such as poly(ethylene glycol)diacrylate (PEGDA) (23), PEGtetrabicyclononyne (24) or composite materials such as polyethylene glycol (PEG)-fibrinogen (25). Incorporating natural polymers is crucial in providing cell-adhesion ligands for cell-matrix interactions and biochemical signaling in the microenvironment to induce angiogenesis postimplantation.…”
Section: Micropatterned Microvasculaturementioning
confidence: 99%
“…The degraded hydrogel is then flushed out of the construct to generate microchannels. Hydrogels used for laser degradation can be made from natural polymers such as silk (20), collagen (21,22) and elastin (22), synthetic polymers such as poly(ethylene glycol)diacrylate (PEGDA) (23), PEGtetrabicyclononyne (24) or composite materials such as polyethylene glycol (PEG)-fibrinogen (25). Incorporating natural polymers is crucial in providing cell-adhesion ligands for cell-matrix interactions and biochemical signaling in the microenvironment to induce angiogenesis postimplantation.…”
Section: Micropatterned Microvasculaturementioning
confidence: 99%
“…Microstructured scaffolds might be useful to mimic bigger structures, such as the bands of Büngner, encouraging axonal regrowth during peripheral nerve regeneration (Bozkurt et al, 2012;Gnavi et al, 2015). Thanks to several manufacturing processes like laser surface texturing, chemical substances, plasma treatment, electrospinning or use of a mold, changes in roughness can be made for most of the available biomaterials (Kim et al, 2016;Berkovitch et al, 2018;Chen et al, 2019).…”
Section: Biomaterials Characteristics To Be Used As a Nerve Conduitmentioning
confidence: 99%
“…As well as for its high biocompatibility, fibrin can be used as a scaffold in tissue engineering thanks to its versatility, indeed its dissolving and coagulation characteristics can be modified by changing the dilution (Bensaïd et al, 2003;Fang et al, 2004). Thanks to fibrin adhesive characteristics, this type of conduit could be not sutured; nevertheless, a recent study demonstrated that sutureless nerve repair with fibrin conduit fails to maintain nerve connections due to poor mechanical stretch resistance (Wang et al, 2018b).…”
Section: Fibrinmentioning
confidence: 99%
“…The distance between the channels was 200 μm, which also guided the hydrogel. It promotes uniform tissue propagation during nerve regeneration [ 100 ].…”
Section: The Synthesis and Modification Of Fibrin Hydrogelsmentioning
confidence: 99%